Defective NOTCH signalling drives smooth muscle cell death and differentiation in bicuspid aortic valve aortopathy. (25th January 2019) - Harrison, Oliver J; Torrens, Christopher; Salhiyyah, Kareem; Modi, Amit; Moorjani, Narain; Townsend, Paul A; Ohri, Sunil K; Cagampang, Felino
Abstract: OBJECTIVES: Bicuspid aortic valve disease is common and is associated with ascending aortic aneurysms. Vascular smooth muscle cell (VSMC) apoptosis is characteristic of the ascending aorta of bicuspid patients, and NOTCH1 gene mutations have also been linked to the disease. NOTCH signalling is a fundamental cell signalling pathway, which dictates cell fate decisions including apoptosis. Our objective was to elucidate the role of NOTCH signalling in VSMC apoptosis and differentiation in bicuspid aortopathy. METHODS: Ascending aortic biopsies were obtained from 19 bicuspid and 12 tricuspid aortic valve patients and were sub-classified into 4 groups according to the maximum ascending aortic diameter (aneurysmal  ≥45 mm). Apoptotic VSMCs were counted by light microscopy using a TUNEL assay. Gene expression of key regulators of NOTCH signalling ( NOTCH1 and HES1 ), apoptosis ( BAX and BCL-2 ) and VSMC differentiation ( MYH11, CNN1 and MYH10 ) were quantified using quantitative real-time PCR. Primary VSMCs were cultured from 2 tricuspid aortic valve and 2 bicuspid aortic valve patients, NOTCH signalling was inhibited with N-[N-(3, 5-Difluorophenacetyl)-l-alanyl]-S-phenylglycine t-butyl ester, and the gene expression was again quantified. RESULTS: The apoptotic cell count was significantly higher in bicuspid aortic valve patients (3.2 cells/50 000 μm 2 vs 1.1 cells/50 000 μm 2 ; P  = 0.033). There was a trend towards lower apoptotic cell count in the aneurysmal versus non-aneurysmal tricuspid and bicuspid groups and an increased ratio of proapoptotic gene expression, which was not statistically significant. This was associated with a 2.8-fold increase in contractile gene expression ( P  = 0.026) and a 2.0-fold increase in NOTCH signalling gene expression in bicuspid versus tricuspid aortic valve patients ( P  =   0.022). NOTCH inhibition in cultured VSMCs induced a similar pattern of increased proapoptotic and procontractile gene expressions. CONCLUSIONS: This preliminary study suggests that NOTCH activation in the non-aneurysmal bicuspid aortas may underlie aortopathy by influencing VSMC apoptosis and differentiation. NOTCH signalling manipulation may provide a therapeutic target for preventing aneurysms in bicuspid patients. Further studies with larger sample sizes are needed to substantiate the present findings.